Issues in Trade Performance of Livestock in India: Reflection of SPS Measures and International Relations: Challenges and Suggestions for Livestock Trade Performance in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is an important member of the world trading community. It is the largest producer of somefoods products in the world.In the current context of liberalization and increasing global integration ofeconomies, it would be unfair to compare livestock sector of India with that obtaining in most of the vastlymodern and technologically far advanced western block countries in terms of a produce that is globallycompetitive. However, despite several weaknesses in terms of adoption of improved technique, the shareof livestock in gross output of agriculture and allied activities has been showing a growing trend duemainly to dependence of millions of Indian farmers on this secondary remunerative source ofagricultural income. Thereby, the paper focuses on the challenges to India’s live stock exchanges whichis centred on the SPS measures of developed countries and are in most cases stringent or higher thaninternational standards.In light of this context, the article makes an effort to evaluate not only the importance of the livestockindustry to the domestic economy but also the potential effects of economic reform under the WTOframework on the local market. It is believed that the free-trade framework established by the WTOpresents many possibilities as well as risks for India's livestock sector. The study draws attention to anumber of concerns that must be addressed in order to maintain India's livestock industry in the WTOage, when wealthy nations' livestock are lavished with care at the expense of hundreds of thousands offarmers in poor nations. The author also compares the India’s position with its international counterpartsin terms of live stock exchange standards and thereby based on it tries to put forward somesuggestions.